A Proposed Technique to Generate Improvement Decisions in Public Sector Innovation in Indonesia: A Case Study of Indonesian Food and Drug Authority (FDA) Provincial Office in Pontianak - Chatulis Indra Jaya; Eko Agus Prasetio (Journal of International Conference Proceedings, 2021)
The goal of this work is to introduce the Gap Analysis technique as a tool for analyzing perception index of public service innovation measurement data using the measurement instrument provided by the State Administration Agency (LAN) of Indonesia. Customers who use public services are asked their perception regarding public service innovation, which is organized by the Indonesian FDA Provincial office in Pontianak through a survey that uses questionnaires consisting of 23 questions. Improvement Gap analysis is modified to propose a gap analysis technique that can adopt a LAN measurement tool. The result shows how the elements of innovation perform, the dissatisfaction perception level, and the gap between current perception and the targeted category of innovation perception. Furthermore, the two-dimensional matrix was able to distinguish four areas for improvement, namely: critical, keep performance, neutral, and exciting elements. The findings of this study show that, besides the private sector's role and public involvement in the process and or quality improvement of service, uniqueness, new kinds of service, service consistency, and service facilities are the critical elements that need to be improved to achieve excellent innovation perception. Thus, the Indonesian government could be able to adopt the modified technique as a tool that provides decision priority to improve public service innovation performance.